2021
DOI: 10.1038/s41598-020-80424-9
|View full text |Cite|
|
Sign up to set email alerts
|

Low melting oxide glasses prepared at a melt temperature of 500 °C

Abstract: Transparent low-melting inorganic glass is an attractive industrial material based on its high thermal and light resistance compared with conventional engineering plastics. If the melting temperature of inorganic glass could be decreased, the doping of guest materials or compression moulding on the glass surface would be easier. Although phosphate glass is considered as a potential candidate because of its transparency in the visible region and low-melting behaviour, water durability often becomes a problem fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…We selected low–melting point phosphate glass particles (a eutectic mixture of different dielectric oxides, including P 2 O 5 , SiO 2 , Al 2 O 3 , Na 2 O, K 2 O, and B 2 O 3 ) to form a framework for the cooling glass coating because of the material’s high durability, low softening temperature ( 39 ), and rich infrared-active vibrational modes, such as Al−O, Si−O, P−O, etc. (fig.…”
Section: Modeling To Guide the Designmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected low–melting point phosphate glass particles (a eutectic mixture of different dielectric oxides, including P 2 O 5 , SiO 2 , Al 2 O 3 , Na 2 O, K 2 O, and B 2 O 3 ) to form a framework for the cooling glass coating because of the material’s high durability, low softening temperature ( 39 ), and rich infrared-active vibrational modes, such as Al−O, Si−O, P−O, etc. (fig.…”
Section: Modeling To Guide the Designmentioning
confidence: 99%
“…2D). During sintering, the reduced viscosity of the raw glass, ~100 Pa·s ( 39 ), facilitates rapid merging and bonding of the glass particles. This forms a framework of larger glass clusters (fig.…”
Section: Process and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Even if the durability towards moisture remains poor, Masai et al have recently reported that tin-containing phosphate glasses could exhibit higher thermal and better resistance to UV light degradation than polycarbonates. 6…”
Section: Introductionmentioning
confidence: 99%
“…Even if the durability towards moisture remains poor, Masai et al have recently reported that tin-containing phosphate glasses could exhibit higher thermal and better resistance to UV light degradation than polycarbonates. 6 Soft chemistry offers the opportunity to assemble materials of exotic nature via low-temperature processing. [7][8][9] Considerable efforts have already been devoted to silica-based materials to significantly reduce fabrication temperatures using for instance the sol-gel process.…”
Section: Introductionmentioning
confidence: 99%